The Effect of High-Tech Clusters on the Productivity of Top Inventors: Comment - Wiebe, Michael (American Economic Review, 2026)
Moretti (2021) reports a positive elasticity between technology cluster size and patenting, and uses an event study and instrumental variables regressions to justify a causal interpretation. The event study does not use the variation generated by inventors moving across cities, and the instrument is constructed incorrectly due to a coding error. I run a corrected event study and fix the coding error, and find null effects. The reported elasticity may not be causal. (JEL J24, L60, O31, O34, R32)